Children's Macro-Level Navigation Patterns in Hypermedia and their Relation with Task Structure and Learning Outcomes - Cindy Paans; Inge Molenaar; Eliane Segers; Ludo Verhoeven (EARLI, 2020)
This study investigated macro-level navigation patterns in children's hypermedia learning, and how they related to task structure and learning outcomes. For this purpose, 5th and 6th grade learners performed a hypermedia assignment in which a high (n=57) versus a low (n=54) level of structure was provided. By means of qualitative analyses of their navigation activities, 6 macro-level navigation patterns were distinguished: linear reading, selective reading, video viewing, massed writing, late onset writing, and unpredictable reading. Results showed that the linear reading pattern was more frequent in the high structure environment, and that both the high structure environment and the linear reading pattern were associated with the highest quality of the children's written assignments. Navigation patterns and task structure did not clearly predict children's declarative knowledge gains or knowledge transfer. These findings show that there are multiple ways to navigate through a hypermedia environment, but that these are not all equally successful for learning. Moreover, the provided task structure in the environment may affect the occurrence of successful navigation patterns.